Bioanalytical Method Development And Validation Of Pazopanib Hydrochloride By Uv- Visible Spectrometry And Rp- Hplc In Human Plasma (Journal of Pharmaceutical Negative Results, 2021)
Background: Pazopanib Hydrochloride is Anti-Cancer agent used in the treatment of renal cell cancer and Von Hippel Lindau Disease. Newly method development and validation of Pazopanib Hydrochloride in Human Plasma was carried out using the chromatographic method.Methods: The UV Spectrophotometric developed with chromatographic method involved LC C18 column, using acetonitrile and water containing 0.1 % formic acid in ratio of 80:20:0.1 v/v/v as mobile phase, a flow rate of 1 ml/min, and UV detection at 270 nm.Results: The retention time of plasma & Pazopanib Hydrochloride was found to be 2.2 & 4.4 min, respectively. Linearity was acceptable in the concentration range for UV-visible Spectrometric method 5-25 μg/ml and for RP-HPLC 1-15 μg/ml. The inter day & intraday precision was found less than 2 for UV-visible spectrometry and for RP-HPLC % CV was found less than 15%. The accuracy was found to be 1.8812 and for RP-HPLC mean recovery was found to be 4.8845.Conclusion: we conclude that the method can be useful for routine analysis, bioanalytical studies and therapeutic drug monitoring.